1982
DOI: 10.1172/jci110659
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Superoxide Dismutase against Diabetogenic Drugs

Abstract: A B S T R A C T Copper-zinc superoxide dismutase (SOD) is present in relatively high concentrations in the ,-cells of human islets. The activity of the extracted enzyme is partially inhibited upon incubation with the diabetogenic drugs alloxan, streptozotocin, or Vacor. The role of this enzyme in protecting a-cells against chemically induced diabetes was further investigated.Incubation of intact canine islets with alloxan (0.2 mg/ml) and 4 mM glucose decreased the insulin secretory response by 87% during subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 31 publications
3
54
0
2
Order By: Relevance
“…In vivo, over-expression of Cu/ZnSOD in diabetic animals provides protection against the development of alloxan-or STZ-induced diabetes. Moreover, addition of scavenging agents such as SOD, Catalase (Cat), guanidinoethyldisulphide, and metal chelators prior to alloxan, STZ, or cytokine exposure has prevented b cell death in isolated islets (Gandy et al 1982, Abdel-Rahman et al 1992, Suarez-Pinzon et al 2001. Lower concentrations of H 2 O 2 , however, seem to be involved in the regulation of physiological processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, over-expression of Cu/ZnSOD in diabetic animals provides protection against the development of alloxan-or STZ-induced diabetes. Moreover, addition of scavenging agents such as SOD, Catalase (Cat), guanidinoethyldisulphide, and metal chelators prior to alloxan, STZ, or cytokine exposure has prevented b cell death in isolated islets (Gandy et al 1982, Abdel-Rahman et al 1992, Suarez-Pinzon et al 2001. Lower concentrations of H 2 O 2 , however, seem to be involved in the regulation of physiological processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiments show that transgenic mice with β cell-specific overexpression of Cu/Zn SOD are more resistant to alloxan-induced diabetes (11). Studies with rodents demonstrate that SOD administration can attenuate streptozotocin-induced (STZ-induced) hyperglycemia and diabetes (12)(13)(14). It was previously reported that antioxidant treatment exerts beneficial effects on β cell mass and insulin content in diabetic C57BL/KsJ-db/db mice (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise diabetogenic mechanism of alloxan is not fully understood, there is some evidence indicating that the tissue damage induced by alloxan is mediated through the formation of reactive oxygen species (ROS, Heikkila et al, 1976;Cohen and Heikkila, 1974;Kim et al, 1994;Park et al, 1995). There are many reports that the scavengers of ROS can ameliorate alloxan toxicity in vitro (Gandy et al, 1982;Abdel-Rahman et al, 1992) and in vivo (Grakvist et al, 1981;Heikkila and Cabbat, 1982). Okamoto (1985) proposed that the primary target of ROS produced from alloxan is the DNA of pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%